The new world order : corporate agenda and parallel reality - Yovanovich, Gordana, 1956- (McGill-Queen's University Press, 2003)
The New World Order seeks to reveal the reality and limitations of "the New World Order," the term U.S. President George Bush Sr used to describe the emerging political reality. Since the early 1990s there has been a fundamental but covert shift in the value system of world politics. The post-World War Two era - marked by the implementation of Keynesian welfare state policies - has ended and in its place we have a New World Order that, under the relentless promotion of neoliberalism, encourages states to adopt a destructive agenda